The development of Islamic financial services in Algeria –Al Salam Bank as a model for the period (2008-2021) - boubaya, assam (Journal of Research in Finance and Accounting, 2023)
This study aims to highlight the development of Islamic financial services in Algeria, with Al Salam Bank was taken as a model for the study, by analyzing its annual reports and statistics provided by it during the period 2008-2021, To achieve the aim of the study, the descriptive approach and the analytical approach was used, as well as the historical approach through the study of information and data used and their nature, with the adoption of a case study method. The study found that there has been a development in financial services at Al Salam Bank, through a development in its assets and the volume of funds granted to customers, the volume of attracted deposits, as well as the development in the size of its branches, The study also found that there is a development in the number of bank customers.